2023
DOI: 10.33712/mana.1276099
|View full text |Cite
|
Sign up to set email alerts
|

Öz-Şefkat Konusunda Yayınlanan Makalelerin Bibliyometrik Analizi

Abstract: Bu çalışmanın amacı Türkiye’de 2007-2023 yılları arasında öz-şefkat konusunda yapılmış olan çalışmaları sistematik bir şekilde incelemektir. Bu incelemede, nicel araştırma yöntem türlerinden birisi olan bibliyometrik analiz kullanılmıştır. Araştırma evrenini, DergiPark, TR Dizin ve SOBİAD gibi veri tabanlarında yapılan tarama sonucunda elde edilen toplam 168 çalışma (araştırma makalesi ve derleme) oluşturmaktadır. Araştırmada, amaçlı örnekleme yönteminden faydalanılmış olup verilerin analizinde MAXQDA 2020 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…When examining the literature, it is observed that bibliometric analysis studies have been conducted on various publications such as theses, articles, citations, papers, and journals in different disciplines such as education (Gülmez et al, 2020), marketing (Zeren & Kaya, 2020), and tourism (Yeksan & Akbaba, 2019). In the field of psychology, bibliometric analyses have been conducted on topics such as self-compassion (Karagöz & Uzunbacak, 2023), self-sabotage (Sayıner, 2023), psychological capital (Becan & Dayanç Kıyat, 2021), school psychological counseling (Özteke Kozan, 2020), and emotional intelligence (Hotamışlı & Efe, 2015).…”
Section: In Summarymentioning
confidence: 99%
“…When examining the literature, it is observed that bibliometric analysis studies have been conducted on various publications such as theses, articles, citations, papers, and journals in different disciplines such as education (Gülmez et al, 2020), marketing (Zeren & Kaya, 2020), and tourism (Yeksan & Akbaba, 2019). In the field of psychology, bibliometric analyses have been conducted on topics such as self-compassion (Karagöz & Uzunbacak, 2023), self-sabotage (Sayıner, 2023), psychological capital (Becan & Dayanç Kıyat, 2021), school psychological counseling (Özteke Kozan, 2020), and emotional intelligence (Hotamışlı & Efe, 2015).…”
Section: In Summarymentioning
confidence: 99%
“…Öz-şefkat kavramı temelinde; bir arkadaşımız zor zamanlardan geçerken ona nasıl özenli, anlayışlı, yargısız bir şekilde yaklaşabiliyorsak aynı hassasiyetle bilfiil kendimize de yaklaşabilmektir. Aynı zamanda bireyin acının kaçınılmaz olduğunu, herkes tarafından deneyimlendiğininin farkına varabilmesini kapsamaktadır (Karagöz ve Uzunbacak, 2023).…”
Section: öZ-şefkatunclassified